Indonesian Travel Policy during the Outbreaks: Vaccination and Quarantine Legal Culture and Policy on Indonesian Air Transportation - Annalisa Yahanan; Nurhidayatuloh Nurhidayatuloh; Mada Apriandi; Tongle Si; Murzal Murzal (Universitas Negeri Semarang, 2023)
During the pandemic, the Indonesian government implemented policies to protect citizens from the virus. One such policy mandated the use of the PeduliLindungi application for passengers traveling domestically or internationally by land, sea, or air. The application helps monitor and track the virus's spread, and provides vaccination information. This study examines the government's policies on PeduliLindungi's use and how the existing legal culture relates to vaccination and quarantine within the app. The research methodology employed a doctrinal approach, analyzing laws, concepts, interpretations, and cases. The study found that the PeduliLindungi application is mandatory for all travelers. It allows passengers to access their vaccination status and determines the required quarantine duration. Violating quarantine orders can result in imprisonment and fines, as per Judge Decision No. 21/Pid.S/2021/PN.Tng. However, limited smartphone ownership restricts public access to the app. Therefore, the government must formulate policies that accommodate individuals without smartphones, ensuring their safety while traveling. Public legal awareness and understanding of the PeduliLindungi app's importance are crucial for protecting public health. Strengthening the legal culture is necessary to promote compliance with health guidelines and informed decision-making. By fostering a robust legal culture, individuals will prioritize health measures, safeguarding their well-being and that of the community.